Photoelectron spectroscopy of size-selected boron clusters: from planar structures to borophenes and borospherenes - Wang, Lai-Sheng (International reviews in physical chemistry, 2016)
Photoelectron spectroscopy (PES) in combination with computational chemistry has been used systematically over the past decade to elucidate the structures and chemical bonding of size-selected boron clusters. Small boron clusters have been found to be planar or quasi-planar, consisting of a monocyclic circumference with one or more interior atoms. The propensity for planarity has been found to be a result of both σ and π electron delocalisation over the molecular plane, giving rise to concepts of σ and π multiple aromaticity. In particular, the B 36 cluster has been found to possess a highly stable planar structure with a central hexagonal vacancy. This finding provides the first indirect experimental evidence that single-atom layer boron-sheets with hexagonal vacancies, dubbed 'borophene', are potentially viable. Another exciting discovery has been the observation and characterisation of the first all-boron fullerenes. PES revealed that the cluster consisted of two isomers with very different electron binding energies. Global minimum searches led to two nearly degenerate isomers competing for the global minimum: a quasi-planar isomer with a double hexagonal vacancy and an unprecedented cage isomer. In the neutral, the B 40 cage is overwhelmingly the global minimum, which is the first all-boron fullerene to be observed and is named 'borospherene'. Rapid progresses in our understanding of the structures and bonding of size-selected boron clusters have been made during the past decade, which will be the focus of this review. The recent findings about borophenes and borospherenes have stimulated growing interests in boron clusters and will accelerate the pace of discovery in boron chemistry and nanostructures.